Gastroenterology cases of cutaneous leukocytoclastic vasculitis. - SENTURK, H; KARATOPRAK, CUMALİ; ARABACI, ELİF; ARABACI, ELİF; YILDIZ, KEMALETTİN; YILDIZ, KEMALETTİN; ÇAKIRCA, MUSTAFA; CAKIRCA, MUSTAFA; ÇıKRıKÇıOĞLU, MA; ERGUN, F; DANALIOGLU, A; Karatoprak, CUMALİ; et al. (My University, 2013)
Rarely, leukocytoclastic vasculitis can result from ischemic colitis, inflammatory bowel disease, and cryoglobulinemia. There is no established standard for the treatment of leukocytoclastic vasculitis associated with gastroenterologic diseases. This paper presents three cases of leukoytoclastic vasculitis, each of which is associated with a different gastroenterologic condition: ischemic colitis, Crohn’s disease, and chronic hepatitis C. Each condition went into remission by treatment of leukocytoclastic vasculitis, regardless of the underlying disease.